2021
DOI: 10.3390/ma14133655
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Materials Immobilized within Chitosan: Applications as Adsorbents for the Removal of Aquatic Pollutants

Abstract: Graphene and its derivatives, especially graphene oxide (GO), are attracting considerable interest in the fabrication of new adsorbents that have the potential to remove various pollutants that have escaped into the aquatic environment. Herein, the development of GO/chitosan (GO/CS) composites as adsorbent materials is described and reviewed. This combination is interesting as the addition of graphene to chitosan enhances its mechanical properties, while the chitosan hydrogel serves as an immobilization matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 242 publications
(269 reference statements)
0
12
0
Order By: Relevance
“…Chitosan-graphene oxide composites have been successfully used as proficient sorbent materials for the removal of different pollutants. The results obtained in this field by employing CS_GO systems can be found in a recent review by da Silva Alves et al [22]. For instance, chitosan/polyacrylamide/graphene oxide nanocomposites (CAGs) containing 20% GO were able to reach the maximum absorption capacity of methylene blue, while a removal efficiency of rifampicin of more than 95% was obtained by applying magnetic CS_GO nanocomposites [23,24].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Chitosan-graphene oxide composites have been successfully used as proficient sorbent materials for the removal of different pollutants. The results obtained in this field by employing CS_GO systems can be found in a recent review by da Silva Alves et al [22]. For instance, chitosan/polyacrylamide/graphene oxide nanocomposites (CAGs) containing 20% GO were able to reach the maximum absorption capacity of methylene blue, while a removal efficiency of rifampicin of more than 95% was obtained by applying magnetic CS_GO nanocomposites [23,24].…”
Section: Introductionmentioning
confidence: 91%
“…For CS membrane preparation, the polymer solution was poured into a petri dish (d = 7 cm) and left at room temperature to remove water. To prepare the CS_GO membranes, GO (powder, density 1.8 g/cm 3 , 15-20 sheets, oxidation 4-10%, Sigma So far, as reported in the review by da Silva Alves et al [22], many studies have been carried out on CS/GO systems for their use as adsorbent materials in environmental applications. To compare the performances of our membranes, particularly of the CS_GO_GLU system, with those of other systems investigated in the literature is very difficult.…”
Section: Preparation Of Chitosan and Chitosan Graphene Oxide Membranesmentioning
confidence: 99%
“…Recently, the incorporation of organic/inorganic fillers like silicon, cellulose, and carbon nanotubes is considered as a simple and efficient method to enhance the mechanical performance of hydrogels. − Of all the two-dimensional nanomaterials, graphene and graphene oxide (GO) are the crucial carbon-based nanomaterials because of their many fascinating properties . Especially, GO is a laminated sp 2 -bonded carbon with the feasibility of attaching rich functional groups on its surfaces such as epoxy, hydroxyl, and carboxyl groups. , Unlike graphene, GO can be stable in a variety of solvents and preserve its many virtues including good hydrophilicity, large specific surface area, high modulus and strength, small density, biocompatibility, electroconductivity, and high thermal conductivity. − These advanced characteristics make GO compatible with other substances like polymers, colloids, films, and amphiphilic molecules, and it can be an important module for constructing various supramolecular systems. , Because of its superior mechanical capacities and electroconductivity, researchers have been keenly interested in exploring electronic sensors, energy batteries, and composite materials based on GO.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that HyCNT demonstrated high speci c surface area, which is interesting characteristics for adsorption application [36]. However, these chemical modi cations for chitosan hydrogel suffer from a number of disadvantages including synthesis these materials can be costly and time consuming [37]. In addition, the regeneration of these modi ed materials for adsorption application were very complicated [38].…”
Section: Introductionmentioning
confidence: 99%